The protective impact of growth hormone against rotenone-induced apoptotic cell death via acting on endoplasmic reticulum stress and autophagy axis - ÇOKER GÜRKAN, AJDA (My University, 2023)
Human growth hormone (GH) is crucial modulator of cellular metabolisms, including cell proliferation and organ development, by stimulating insulin-like growth factor-1 (IGF-1), which has various functions such as cell proliferation, tissue growth, survival, or neuroprotection. Therefore, GH is implicated as a critical player in the cell and can enhance neurogenesis and provide neuroprotection during the treatment of neurological diseases such as Parkinson’s disease (PD). In this study, the neuroprotective role of GH was investigated in rotenone-induced PD models for the first time. Both SH-SY5Y and SK-N-AS neuroblastoma cells were exposed to rotenone to mimic PD pathogenesis as stated in previous studies. Our data demonstrated that overexpression of GH led to the resistance of the SH-SY5Y and SK-N-AS cell lines to rotenone treatment. The levels of ER stress markers, CHOP, PERK, XBP-1, and ATF6, were higher in wt cells than GH+ SH-SY5Y cells. However, the level of autophagy markers LC3 increased and the levels of reactive oxygen species (ROS) decreased with the overexpression of GH. Furthermore, while rotenone significantly increased the SubG1 population in the cell cycle of SH-SY5Y wt cells, there was a minor alteration in GH+ cell population. Concomitantly, the levels of the proapoptotic marker, cleaved-PARP, and positive staining of Annexin V in SH-SY5Y wt cells were higher after rotenone treatment. Together, these results revealed that overexpression of GH enhanced the autophagy response by triggering the ER stress of SH-SY5Y cells to rotenone exposure and showed a neuroprotective effect in vitro PD models.
Keywords: Tıp; Histoloji-Embriyoloji; Mikrobiyoloji ve Klinik Mikrobiyoloji; Dahili Tıp Bilimleri; Tıbbi Genetik; Tarımsal Bilimler; Ziraat; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyokimya; Fizyoloji; Temel Bilimler; Medicine; Histology and Embryology; Microbiology and Clinical Microbiology; Internal Medicine Sciences; Medical Genetics; Agricultural Sciences; Agriculture; Life Sciences; Molecular Biology and Genetics; Health Sciences; Fundamental Medical Sciences; Biochemistry; Human Physiology; Natural Sciences; Tarım ve Çevre Bilimleri (AGE); Yaşam Bilimleri (LIFE); Tarım Bilimleri; Biyoloji ve Biyokimya; Mikrobiyoloji; FİZYOLOJİ; HÜCRE BİYOLOJİSİ; MİKROBİYOLOJİ; GENETİK VE KALITIM; ZİRAAT MÜHENDİSLİĞİ; Agriculture & Environment Sciences (AGE); Life Sciences (LIFE); AGRICULTURAL SCIENCES; BIOLOGY & BIOCHEMISTRY; MOLECULAR BIOLOGY & GENETICS; MICROBIOLOGY; PHYSIOLOGY; CELL BIOLOGY; GENETICS & HEREDITY; AGRICULTURAL ENGINEERING; Moleküler Biyoloji; Genetik; Genel Tarım ve Biyoloji Bilimleri; Hücre Biyolojisi; Microbiology; Physiology; Molecular Biology; Genetics; General Agricultural and Biological Sciences; Cell Biology; autophagy; endoplasmic reticulum stress; growth hormone; Parkinson’s disease; Rotenone